2021
DOI: 10.1186/s40068-021-00219-3
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological Drought in Northwestern Escarpment of Ethiopian Rift Valley: detection seasonal and spatial trends

Abstract: Background The Northwestern Escarpment of the Ethiopian Rift Valley has been frequently affected by droughts for decades. The area is among the most drought-prone and chronically food-insecure parts of the country. The study areas that include the Raya Valley livelihood Zone (RVLZ), Alagie-Offla livelihood Zone (ALOFLZ), and Tsirare Catchment Livelihood Zones (TCLZ) are amongst the most vulnerable and badly affected livelihood zones in the Northwestern Escarpment of the Ethiopian Rift Valley. H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Besides, the Wabishebele and Abbay river basins experienced severe drought in the 1980s and 2000s, respectively. The result of hydrological drought analysis using SDI agrees with previous meteorological drought study findings in Ethiopia [ 66 , 67 , 68 , 69 ]. But the result from M1SWSI contrasts with SDI results.…”
Section: Resultssupporting
confidence: 89%
“…Besides, the Wabishebele and Abbay river basins experienced severe drought in the 1980s and 2000s, respectively. The result of hydrological drought analysis using SDI agrees with previous meteorological drought study findings in Ethiopia [ 66 , 67 , 68 , 69 ]. But the result from M1SWSI contrasts with SDI results.…”
Section: Resultssupporting
confidence: 89%
“…Drought is a recurring phenomenon in Ethiopia [13] that signi cantly impacts the socioeconomic sector and various components of the environment [14]. It a ects many sectors, causes large economic losses, and threatens human life and the environment [15].…”
Section: Introductionmentioning
confidence: 99%
“…The timely information on the occurrence of drought and the analysis of the level of farmers' vulnerability is an element of the drought response mechanism. Nasir et al [47] indicated that drought is often returned once it ends and due to this nature, the government will again be misinformed about the time of the next severe drought episode occurrence. Hence, investigating the vulnerability of farmers' livelihood to this nature of recurrent drought helps to devise the response mechanisms.…”
Section: Introductionmentioning
confidence: 99%